CREDIT-MODULE EDUCATIONAL SYSTEM AS WORLD EXPERIENCE (Web of Teachers: Inderscience Research, 2024)
The article discusses the world experience of the credit-module education system. As one of the globalization processes taking place in the world, the implementation mechanism of the “Bologna Process”, which envisages the convergence and harmonization of the higher education systems of European countries in order to create a single European higher education area. The credit-module education system is aimed at personal improvement, organizing independent work and personal development. it is analyzed that teaching independence is the main principle of this form of education. In today’s transition to the credit-module system, the formation of the methodology of independent education of students is of great scientific and practical importance. Organizing students’ independent work, developing a mechanism for its implementation, visual, virtual, technological, informative-digitization in independent work, ensuring the flexibility and variability of independent work trajectories in performing scientific and creative work taking into account the professional interests and wishes of students are among the urgent tasks.